(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
This study examines the effect of Environmental, Social, and Governance (ESG) practices on firm financial performance, in companies listed within the NGO Independent Database during the 2021–2023 period. Using panel regression analysis, the results reveal an asymmetric influence of ESG components. The environmental dimension shows no significant impact on ROA, indicating that environmental investments yield benefits primarily in the long term and are not yet reflected in short-term profitability. The social dimension demonstrates a negative and significant effect, suggesting that expenditures on social initiatives may suppress profits in the short run despite their reputational and relational importance. Conversely, the governance dimension exerts a positive and significant effect on profitability, underscoring that strong governance practices enhance efficiency, transparency, and financial outcomes. These findings contribute to ESG scholarship in emerging markets by highlighting the trade-offs between short-term financial performance and long-term sustainability. The results also offer practical implications for corporate managers, investors, and policymakers to strategically balance sustainability goals with profitability.